Authenticity and integrity in civil electronic contracting: Analysis of its problems and proposal de lege ferenda for its incorporation into the Peruvian Civil Code. - Cordero Mendoza, Liliana Katherine (Revista de Derecho, 2024)
The author examines the issue of authenticity and integrity in electronic communication and its impact on civil contracts. Among the solutions proposed by Peruvian law regarding the treatment of electronic contracts, the contribution provided by the second paragraph of Article 51 of the Commercial Code stands out. This Article, understood in a broad and general sense, can be applied to current electronic contracts. Additionally, the author proposes incorporating a similar provision into the Peruvian Civil Code to ensure the reliability of informal civil contracts.